2011
DOI: 10.1017/s1751731110002211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maize silage to grass silage ratio and feed particle size on ruminal fermentation in vitro

Abstract: The effect of the forage source on ruminal fermentation in vitro was investigated for fine (F) and coarse (C) milled diets, using a modified Hohenheim gas production test and a semi-continuous rumen simulation technique (Rusitec). It was hypothesised that the replacement of maize silage by grass silage might lead to associative effects and that interactions related to particle size variation could occur. Five diets with a maize silage to grass silage ratio of 100 : 0, 79 : 21, 52 : 48, 24 : 76 and 0 : 100 diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 31 publications
3
18
0
Order By: Relevance
“…High proportions of concentrate in the diet (Ranilla and Carro, 2003) and supplementation of maize starch to grass pasture (Bach et al, 1999) were reported to reduce the N content in the microbial mass. Changes in the availability of nutrients, as described between treatments F and C (Hildebrand et al, 2010), did not affect N contents of the microbial fractions. Changes in the availability of nutrients, as described between treatments F and C (Hildebrand et al, 2010), did not affect N contents of the microbial fractions.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…High proportions of concentrate in the diet (Ranilla and Carro, 2003) and supplementation of maize starch to grass pasture (Bach et al, 1999) were reported to reduce the N content in the microbial mass. Changes in the availability of nutrients, as described between treatments F and C (Hildebrand et al, 2010), did not affect N contents of the microbial fractions. Changes in the availability of nutrients, as described between treatments F and C (Hildebrand et al, 2010), did not affect N contents of the microbial fractions.…”
Section: Discussionmentioning
confidence: 75%
“…Similar amounts of total short-chain fatty acids indicated that the amount of fermented carbohydrates was similar between diets of different maize silage to grass silage ratio (Hildebrand et al, 2010). The amount of ATP derived from Sum of the 15 analysed AA.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations